ส่วนประสมการตลาดที่มีผลต่อผู้บริโภคในอำเภอเมืองเชียงใหม่ในการใช้บริการอาหารบุฟเฟ่ต์โรงแรม - เสาวภา เชิดสถิรกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study aimed to examine marketing mix affecting consumers in Muang Chiang Mai district towards using hotel buffet services. Data were collected from 385 customers using hotel buffet services within a year ago and residing in Mueang Chiang Mai district. Data obtained were, then, analyzed by the descriptive statistics, including frequency, percentage, and mean. Hereafter were shown the summary for the studied results. The findings presented that most respondents were female in the age ranges of under 21 years old, 21-30 years old, 31-40 years old, and 41-50 years old. They were single and carried bachelor’s degree as the highest educational background. The worked as private company employee whose gross monthly income was less than 10,000 Baht. Person joining them to use the hotel buffet services was friend. Type of buffet that they used was the international buffet. Reason in using buffet services at the hotel in Mueang Chiang Mai district was the confidence in its taste. Person influencing their selection of hotel buffet was friend. They usually took dinner buffet mostly on Saturday at an uncertain chance. They mostly used the buffet services at Holiday Inn hotel with the frequency of once in over 3 months and spent 351-450 Baht per person per time or the buffet. Source of information where they learned about the hotel buffet service was the recommendation from others. Regarding the study on marketing mix affecting consumers in Mueang Chiang Mai district towards using hotel buffet services, the results revealed that people factor was rated at the highest level; while factors namely service process, product or service, physical evidence and presentation, place, and price were rated at high level respectively. Promotion factor was, however, rated at moderate level. Hereafter were shown sub-factors that were rated at the highest level. The product or service factor was the freshness and the cleanliness of food. The price factor was the reasonable price of the buffet service comparing to its quality and services. The place factor was the large and sufficient parking space. The promotion factor was the cash discount for regular customers. The people factor was the honesty of staff to customers such as to inform customers who did over payment immediately. The service process factor was the well preparedness of food which was continually added for all customers. The physical evidence and presentation factor was the cleanliness of toilets available in the restaurant area.